Control strategy for effective battery utilization in a stand-alone DC microgrid with solar energy - Yan, Hein Wai (2022)
DC microgrids with photovoltaic (PV) systems often incorporate a battery energy storage system (BESS) to regulate the dc bus voltage fluctuations due to the intermittent irradiance changes and load transients. Traditional control schemes do not consider the battery charging rate, leading to high current stress and shortening the battery lifetime. In this paper, a coordinated control for a PV system and the BESS is proposed, which implements a deterministic rule-based control strategy that regulates the battery charging rate depending on the available PV power reserve and the battery state-of-charge. Furthermore, the proposed control considers the PV system as the primary dc voltage regulator and treats the BESS as a secondary voltage regulating resource. The performance of the proposed control is investigated via simulation results.